2019
DOI: 10.1111/os.12532
|View full text |Cite
|
Sign up to set email alerts
|

Hip Replacement as Alternative to Intramedullary Nail in Elderly Patients with Unstable Intertrochanteric Fracture: A Systematic Review and Meta‐Analysis

Abstract: ObjectiveTo evaluate the efficacy and safety of hip replacement and intramedullary nails for treating unstable intertrochanteric fractures in elderly patients.MethodsRandomized clinical trials (RCTs) to compare hip replacement with intramedullary nail in the management of elderly patients with unstable intertrochanteric femur fracture were retrieved from Cochrane Library (up to January 2018), CNKI (China National Knowledge Infrastructure), Wanfang Data, PubMed, and Embase. The methodological quality of the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 23 publications
3
35
0
8
Order By: Relevance
“…Therefore, hemiarthroplasty is emerging as a viable alternative to internal fixation in recent decades. [1][2][3][4][5][6]8,[10][11][12] In this study, we retrospectively followed up 22 elderly patients of unstable intertrochanteric fractures treated by cemented bipolar hemiarthroplasty as the primary management plan. We observed that, hemiarthroplasty in the unstable fracture scenario is more challenging than the routine hemiarthroplasty surgeries for fractures of the neck of femur.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, hemiarthroplasty is emerging as a viable alternative to internal fixation in recent decades. [1][2][3][4][5][6]8,[10][11][12] In this study, we retrospectively followed up 22 elderly patients of unstable intertrochanteric fractures treated by cemented bipolar hemiarthroplasty as the primary management plan. We observed that, hemiarthroplasty in the unstable fracture scenario is more challenging than the routine hemiarthroplasty surgeries for fractures of the neck of femur.…”
Section: Discussionmentioning
confidence: 99%
“…Intertrochanteric fractures are the commonest fractures in the elderly patients. 1 The incidence of these injuries is increasing every year and is expected to be doubled by the year 2040. 2,3 These fractures are often complicated by medical co-morbidities like diabetes, hypertension, osteoporosis, renal diseases and chronic lung diseases making them prone to complications of prolonged confinement to bed, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations